Ultrasonic Surface Treatment of Titanium Alloys. The Submicrocrystalline State - Klimenov V. A. Vasily Aleksandrovich; Vlasov V. A.; Borozna V. Yu. Vyacheslav Yurievich; Klopotov A. A. (Innovative technologies for producing and machining materials in mechanical engineering, 2015)
Title screen